Pembentukan Komunitas Peduli Hipertensi pada Masyarakat Desa Tani Bhakti, Kab. Kutai Kartanegara - Rahayu, Eka Putri; Chifdillah, Nino Adib; Tonapa, Emelia (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The aim of this activity was to increase partner knowledge, skills and services by empowering communities in controlling hypertension through the Hypertension Care Community in the Tani Bhakti Village, Kutai Kartanegara regency Methodology: This community empowerment consists of community building called “”Komunitas Peduli Hipertensi”, health education, training of digital tensimeter and prolanis exercise. Results: The results of this community empowerment was the establishment of a hypertension community care. The enthusiasm of participants was also very high participating in every activities held by. These activities were health education, prolanis exercise and digital tensimeter training for cadre. Conclusions: Community service activities in Tani Bhakti Village, Kutai Kartanegara Regency were carried out well. There were 4 activities carried out, namely the formation of a hypertension care community, health education about hypertension, hypertension prolanis gymnastics and digital tensiometer training. Limitations: The participants was limited to adult only so it did not include all residents with age-representative who live in Tani Bhakti Village. Contributions: This community service activity can have positive impact on the people who live in Tani Bhakti Village. These activity used in hypertension care management.